1985
DOI: 10.1099/0022-1317-66-9-1901
|View full text |Cite
|
Sign up to set email alerts
|

The Coexistence of Multiple Bluetongue Virus Electropherotypes in Individual Cattle during Natural Infection

Abstract: SUMMARYEvidence of multiple genotypes of bluetongue virus (BTV) serotype 11 simultaneously infecting individual cattle was demonstrated in a California sentinel herd naturally infected with two BTV serotypes (11 and 17). Monitoring of weekly virus isolates by PAGE demonstrated genome segment diversity among BTV serotype 11 isolates and an individual bull simultaneouSly infected with multiple electropherotypes of this serotype. No electrophoretic variations were apparent in BTV serotype 17 isolates. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 33 publications
0
20
1
Order By: Relevance
“…This has been shown to occur experimentally in dually infected ruminants. 17 Our results differ from those of Oberst et al 16 in that the double-banded electropherotype reported here was stable over a period of 4 years. In the present study, single-banded variants of the doublebanded electropherotypes could only be isolated after extensive serial plaque purifications, and reassortant strains could not be demonstrated in ruminants.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This has been shown to occur experimentally in dually infected ruminants. 17 Our results differ from those of Oberst et al 16 in that the double-banded electropherotype reported here was stable over a period of 4 years. In the present study, single-banded variants of the doublebanded electropherotypes could only be isolated after extensive serial plaque purifications, and reassortant strains could not be demonstrated in ruminants.…”
Section: Discussioncontrasting
confidence: 57%
“…3 It has been shown that viral strains of a single serotype, exhibiting more than 1 electropherotype, may coexist within a single animal or herd. 3,16 In addition, predominant electropherotypes have been shown to change during the course of a single bluetongue outbreak. 3 We report here the genetic transitions of BTV Received for publication May 20, 1988. infecting domestic ruminants in eastern Colorado over a 4-year period and the continued predominance of an electropherotype apparently resulting from multiple infections.…”
mentioning
confidence: 99%
“…Thus, an individual fly could become mixedly infected with different BTV strains by sequential feeding on hosts viraemic for different viruses, or by feeding on a single mixedly infected vertebrate host. The feasibility of either mode of acquiring a mixed infection is supported by the presence of multiple BTV serotypes in many infected herds (Osburn et al, 1981) and the recovery of multiple serotypes from individual infected sheep and cattle (Stott et al, 1982;Oberst et al, 1985). The genetic consequence of mixed BTV infection of C. variipennis is not known.…”
Section: -7646 © 1987 Sgm S K Samal and Othersmentioning
confidence: 99%
“…This has previously been described for bluetongue virus (Squire et al, 1983;Oberst et al, 1985;Knudson et al, 1982).…”
Section: All Of the Zimbabwe Isolates Cross-reacted With Each Other Imentioning
confidence: 99%